PrbP modulates biofilm formation in Liberibacter crescens - Lei Pan; Christopher L. Gardner; Reagan Beliakoff; Danilo da Silva; Ran Zuo; Fernando A. Pagliai; Kaylie A. Padgett‐Pagliai; Marcelo L. Merli; Erol Bahadiroglu; Claudio F. Gonzalez; Graciela L. Lorca (Environmental Microbiology, 2021)
Summary In Liberibacter asiaticus , PrbP is a transcriptional regulatory protein involved in survival and persistence during host infection. Tolfenamic acid was previously found to inhibit interactions between PrbP and the promotor region of rplK , resulting in reduced survival of L . asiaticus in the citrus host. In this study, we performed transcriptome analyses to elucidate the PrbP regulon in L . crescens , as it is phylogenetically the closest related species to L . asiaticus that can be grown in laboratory conditions. Chemical inhibition of PrbP with tolfenamic acid revealed that PrbP is involved in the regulation of diverse cellular processes, including stress response, cell motility, cell cycle and biofilm formation. In vitro DNA binding and bacterial two‐hybrid assays also suggested that PrbP is a global regulator of multiple transcription factors (RpoH, VisN, PleD, MucR, MocR and CtrA) at both transcriptional and/or post‐transcriptional levels. Sub‐lethal concentrations of tolfenamic acid significantly reduced the attachment of L . crescens during biofilm formation and decreased long‐term persistence in biofilm structures. Overall, our findings show the importance of PrbP in regulating diverse biological processes through direct and indirect interactions with other transcriptional regulators in L . crescens .

Identification of flavonoids as regulators of YbeY activity in Liberibacter asiaticus - Ran Zuo; Aline de Oliveira; Enrica Bullita; Maria Ines Torino; Kaylie A. Padgett‐Pagliai; Christopher L. Gardner; Natalie A. Harrison; Danilo da Silva; Marcelo L. Merli; Claudio F. Gonzalez; Graciela L. Lorca (Environmental Microbiology, 2019)
Summary Liberibacter asiaticus is the prevalent causative pathogen of Huanglongbing or citrus greening disease, which has resulted in a devastating crisis in the citrus industry. A thorough understanding of this pathogen's physiology and mechanisms to control cell survival is critical in the identification of therapeutic targets. YbeY is a highly conserved bacterial RNase that has been implicated in multiple roles. In this study, we evaluated the biochemical characteristics of the L . asiaticus YbeY (CLIBASIA_01560) and assessed its potential as a target for antimicrobials. YbeY Las was characterized as an endoribonuclease with activity on 3′ and 5′ termini of 16S and 23S rRNAs, and the capacity to suppress the E . coli ΔybeY phenotype. We predicted the YbeY Las protein:ligand interface and subsequently identified a flavone compound, luteolin, as a selective inhibitor. Site‐directed mutagenesis was subsequently used to identify key residues involved in the catalytic activity of YbeY Las . Further evaluation of naturally occurring flavonoids in citrus trees indicated that both flavones and flavonols had potent inhibitory effects on YbeY Las . Luteolin was subsequently examined for efficacy against L . asiaticus in Huanglongbing‐infected citrus trees, where a significant reduction in L . asiaticus gene expression was observed.